Hydro-electric unit commitment subject to uncertain demand - Philpott, A.B.; Craddock, M.; Waterer, H. (European journal of operational research, 2000)
We consider the problem of scheduling daily hydro-electricity generation in a river valley. Each generating station in this river valley has a number of turbines which incur fixed charges on startup and have a generation efficiency which varies nonlinearly with flow. With appropriate approximations the problem of determining what turbine units to commit in each half hour of the day can be formulated as a large mixed-integer linear programming problem. In practice the generation required from this group of stations in each half hour is often different from that forecast. We investigate the impact of this uncertainty on the unit commitment by using an optimization-based heuristic to give an approximate solution to the stochastic problem.